Icariside II, a Broad-Spectrum Anti-cancer Agent, Reverses Beta-Amyloid-Induced Cognitive Impairment through Reducing Inflammation and Apoptosis in Rats - Deng, Yuanyuan; Long, Long; Wang, Keke; Zhou, Jiayin; Zeng, Lingrong; He, Lianzi; Gong, Qihai (Frontiers in Pharmacology, 2017)
Beta-amyloid (Aβ) deposition, associated neuronal apoptosis and neuroinflammation are considered as the important factors which lead to cognitive deficits in Alzheimer’s disease (AD). Icariside II (ICS II), an active flavonoid compound derived from Epimedium brevicornum Maxim, has been extensively used to treat erectile dysfunction, osteoporosis and dementia in traditional Chinese medicine. Recently, ICS II attracts great interest due to its broad-spectrum anti-cancer property. ICS II shows an anti-inflammatory potential both in cancer treatment and cerebral ischemia-reperfusion. It is not yet clear whether the anti-inflammatory effect of ICS II could delay progression of AD. Therefore, the current study aimed to investigate the effects of ICS II on the behavioral deficits, Aβ levels, neuroinflammatory responses and apoptosis in Aβ25-35-treated rats. We found that bilateral hippocampal injection of Aβ25-35 induced cognitive impairment, neuronal damage, along with increase of Aβ, inflammation and apoptosis in hippocampus of rats. However, treatment with ICS II 20 mg/kg could improve the cognitive deficits, ameliorate neuronal death, and reduce the levels of Aβ in the hippocampus. Furthermore, ICS II could suppress microglial and astrocytic activation, inhibit expression of IL-1β, TNF-α, COX-2 and iNOS mRNA and protein, and attenuate the Aβ induced Bax/Bcl-2 ratio elevation and caspase-3 activation. In conclusion, these results showed that ICS II could reverse Aβ-induced cognitive deficits, possibly via the inhibition of neuroinflammation and apoptosis, which suggested a potential protective effect of ICS II on Alzheimer’s disease.